Hirarc study for occupational safety and health evaluation of clinical waste handlers at a hospital and an incineration plant / Kauselya Muniandy - Muniandy, Kauselya (2015)
Clinical waste poses serious threats and hazards to human health. Clinical waste, which is categorized as a scheduled waste in Malaysia, has been increasing over the years. Thus, proper clinical waste management is important as improper clinical waste handling has led to many incidents involving handlers over the years (Arab et al., 2008). However, research on hazard and risk assessment for clinical waste management has been very limited, and there is a serious dearth of information for risk control planning. This project seeks to document the hazards found during clinical waste collection and disposal practices in a healthcare establishment and hazards involving the operators at a clinical waste treatment incinerator. Along with hazard identification, a quantitative risk assessment has been done to prioritize the risk control management. Hospital Raja Permaisuri Bainun, Ipoh was selected for this study to evaluate the safety and health hazards associated with daily clinical waste collection and disposal activities. The clinical waste management in this hospital is handled by a private concessionary company appointed by Ministry of Health, Malaysia. The study reveals that the clinical waste handlers were exposed to some hazards during handling of clinical waste. This includes biological, chemical, physical, mechanical and ergonomic hazards. Out of 10 identified hazards, 40% posed high level risk and another 60% posed medium level risk. The major hazard found was biological hazard which contributes to 100% of high level risk. Accident records show needle prick injuries often involves the clinical waste handlers. Usage of PPE and administrative control are main mitigation measures implemented at the hospital. iv The study shows no frequent training courses were organized by the management to create awareness among the employees. The risk assessment by the safety committee was also not done quantitatively to prioritize the risk management. Secondly, an incineration plant treating clinical waste was selected for this study to evaluate the occupational safety and health risk management at the plant. A total of 82 safety and health hazards identified at the plant were then classified as physical, mechanical, electrical, chemical, biological, ergonomic and psychological. 19% of the hazards posed high risk followed by 49% of medium risk hazards and another 32% of low risk hazards. Existing risk control measures includes engineering control measures such as installation of machine guards, usage of PPE and some administrative controls are implemented at the plant. The hazard and risk management at this plant is in accordance with Malaysian Occupational Safety and Health Act. However, some deficiencies observed could be improved through better risk control implementation. Internal air quality inspection and detailed comparative analysis on medical records of workers was suggested for better control of the risk. It was noticed that some small accidents were not recorded and analysed accordingly. Unless there are strong measures put in place as recommended in this study, the rise in safety and health risk due to mismanagement of clinical waste will increase and may become a serious problem in future.